Measuring 25-hydroxyvitamin D in cats: comparison of a whole-blood lateral flow assay, 2 dried-blood-spot tests, and serum LC-MS/MS. (May 2023) - Brodlie, Hannah; Quimby, Jessica; Rudinsky, Adam J.; Paschall, Rene E.; Brusach, Katelyn; Klein, Hannah; Winston, Jenessa A.; Parker, Valerie J.
Measuring 25-hydroxyvitamin D (25D) can be a challenge in veterinary medicine because of laboratory accessibility and required sample volume. We compared 2 dried-blood-spot (DBS) tests and a lateral flow assay (LFA) to the gold standard, liquid chromatography–tandem mass spectrometry (LC-MS/MS). We hypothesized that there would be good agreement among the tests, within a clinically significant limit of agreement of ± 25 nmol/L. We collected blood from 6 healthy purpose-bred 2-y-old cats at 6 times over 6 wk, and measured 25D concentrations with all 4 tests. Agreement of the 3 candidate tests and LC-MS/MS was evaluated via Bland–Altman analysis, Passing–Bablok regression, and Lin correlation coefficients. Bland–Altman analysis demonstrated that the mean bias was >± 25 nmol/L for all 3 candidate tests in comparison to serum LC-MS/MS concentrations. The 95% CIs for the mean bias did not include zero, further supporting the presence of significant bias among methods. Additionally, all 3 tests had poor agreement with serum LC-MS/MS concentrations when analyzed by Lin correlation coefficient analysis, and bias between methods was further characterized by Passing–Bablok analysis. Based on these results, none of these 3 tests is recommended as an alternative to LC-MS/MS testing for 25D measurement in cats.